2009 Latin American Web Congress 2009
DOI: 10.1109/la-web.2009.33
|View full text |Cite
|
Sign up to set email alerts
|

Towards Canonical Task Types for User Interface Design

Abstract: Abstract-Task models are the cornerstone of user-centred design methodologies for user interface design. Therefore, they deserve attention in order to produce them effectively and efficiently, while guaranteeing the reproducibility of a task model: different persons should in principle obtain the same task model, or a similar one, for the same problem. In order to provide user interface designers with some guidance for task modelling, a list of canonical task types is proposed that offers a unified definition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In software engineering, a specification-based (or model-driven) approach relies on the power of models to construct and reason about software systems. Our approach to build the architecture is based on models, and we use UML diagrams to express them, as well as task models [43] with canonical task definitions [44] as a baseline to document user needs and interaction in the user interface. The benefit of developing software with a rational set of principles includes, but is not limited to, reproducibility and its orientation towards quality criteria.…”
Section: Home Energy Management System With Iot Demand System Archite...mentioning
confidence: 99%
See 1 more Smart Citation
“…In software engineering, a specification-based (or model-driven) approach relies on the power of models to construct and reason about software systems. Our approach to build the architecture is based on models, and we use UML diagrams to express them, as well as task models [43] with canonical task definitions [44] as a baseline to document user needs and interaction in the user interface. The benefit of developing software with a rational set of principles includes, but is not limited to, reproducibility and its orientation towards quality criteria.…”
Section: Home Energy Management System With Iot Demand System Archite...mentioning
confidence: 99%
“…The results of the process are the vision board of the project, PERSONAS, user need, and functionalities, and the value added to user's life is written at the end. Functionality is defined by working around ca nonical task types [44]. Tasks were defined in the previous steps; at this point, the question is how they are going to be implemented.…”
mentioning
confidence: 99%
“…For our study, we selected a set of 30 commands for common interactions from the current literature, which were divided into four groups, along with their referents, which were presented with a stimulus before and after the command ( Fig. 12): a group of 4 basic commands (''Turn light on/off'' and ''Brighten/dim light'') [23], [47], a group of 13 selection commands (e.g., ''Select a date in digital/analog format'') [48], a group of 9 commands that are based on sets (e.g., ''Expand/collapse a set of menu items'', ''Select an item from the full set of data'', and ''Select (again) from the selected subset'') [48], [49], and a group of 4 referents for specification (''Specify a position, a direction, a translation, and a rotation'') [50]. These tasks have been chosen to cover an increasing number of dimensions, from 0D (e.g., ''Turn light on''), 1D (e.g., ''Dim light''), and 2D (e.g., ''Specify a position''), to 2D1/2 (e.g., ''Specify a translation'').…”
Section: Confirmatory Studymentioning
confidence: 99%
“…Hearst et al showed that faceted navigation is an effective method that can be helpful during a design activity [14]. CHIDeK's facets are based on: task types based on the work of Gonzalles-Caleros et al [15], which are verbs, such as search or navigate; design artifacts, such as screenshots or documents; UI widgets, such as buttons and text fields; and UI patterns extracted from UI pattern libraries, 1,2 such as wizard and breadcrumbs. The task types facets were created to give the designer an option to browse cases adopting a problembased approach or using a more abstract representation than widgets, whereas the UI patterns and widgets facets were created to provide a more concrete representation when following a solution-based approach.…”
Section: The Case Library Shows the Title Of The Cases And A Small Thmentioning
confidence: 99%